Application of Flowmeter Sensor Technology in Ship Auxiliary Engines for Improved Energy Efficiency in the Maritime Community Based on PLC Technology - Anggara Trisna Nugraha; Chusnia Febrianti (Politeknik Perkapalan Negeri Surabaya, 2024)
The container transport system plays a crucial role in facilitating cargo transfer by simplifying the unloading process to make it more effective and efficient. In container vessel operations, fuel consumption management is a critical aspect that significantly impacts operational costs, accounting for approximately 70% of the total expenses. Therefore, shipping companies must closely monitor fuel consumption to prevent wastage. Without an effective monitoring system, the management cannot track fuel consumption in real-time, which may lead to misuse by crew members. This study aims to implement a flowmeter sensor technology based on Outseal PLC for automatic monitoring of fuel consumption on vessels. The data from the flowmeter sensor will be transmitted to a web server, allowing authorized personnel to access the information for transparent and accurate oversight. The test results of the flowmeter sensor show low error rates of 1.23%, 2.07%, and 2.06%. Thus, this system proves to be effective as a real-time fuel consumption monitoring solution for auxiliary engines, with a reading interval of approximately 1 minute and 58 seconds per liter. This research contributes to improving energy efficiency in the maritime sector while empowering the shipping community with technology that can be accessed by relevant parties, as part of a broader community service initiative.